Patients’ Satisfaction of Health Care Services Provided at Out Patient Department of Dhaka Medical College Hospital - Islam, Md Ziaul; Jabbar, Md Abdul (Ibrahim Medical College Journal, 2009)
This descriptive cross sectional study was conducted on 299 patients visiting outpatient department (OPD) of Dhaka Medical College Hospital (DMCH) between November 2005 and April 2006 (6 months) to assess their satisfaction of OPD services. Majority of the patients was male (54.85%) with mean age of 36 years, married (75.92%) with a family size of 5-7; of education level from illiterate to below SSC (71.91%) and from lower (46.44%) and lower middle (38.20%) income group. 53.18% patients visited OPD with medical, followed by surgical (26.76%) and gynaecological (20.06%) problems. The main reasons for choosing DMCH were effective (32.78%), free (24.41) and/or low cost (18.73%) treatment. There was long waiting time (32 minutes). However majority of the patients (81.14%) expressed satisfaction (ranging from fair to good) with respect to adequacy of space, sitting arrangement and cleanliness of the waiting rooms, but were dissatisfied (75.31%) with respect to toilet facilities and supply of drinking water. 74.90% patients were satisfied (ranging from fair to good) with OPD staffs with respect to their availability and readiness to register and make appointment with doctors. However 41.06% were dissatisfied with respect to their willingness to listen with compassion and reassure the patients with their problems. Only 65.1% patients received prescribed drugs from hospital pharmacy and majority of them were dissatisfied with respect to information provided about medication use (58.80%) and side-effects (98.70%). Of the patients advised to have laboratory investigations only 37.61% got them done at OPD laboratory and 59.75% of them were satisfied with the laboratory services. Women were more satisfied with OPD services compared to their male counterparts (χ2, p<0.05). Patients' satisfaction was inversely related to monthly income (χ2, p<0.05) and level of education (χ2, p<0.05). To improve patients' satisfaction, most of the patients suggested for more doctors and supporting staff, improvement of waiting room facilities, drug supply and laboratory investigations. Ibrahim Med. Coll. J. 2008; 2(2): 55-57 Key Words: Patients' satisfaction, OPD services, socio-economic variables, DMCH doi: 10.3329/imcj.v2i2.2938